DAMPAK PANDEMI COVID-19 TERHADAP PSIKOLOGIS IBU HAMIL - Sari, Yona Wia Sartika; Martha, Evi (LPPM Universitas Prima Nusantara Bukittinggi, 2021)
Background: The COVID-19 pandemic has brought many health problems to the world, even having an impact on a socio-economic crisis that has a negative psychosocial effect on everyone, including pregnant women. Several studies have shown that the COVID-19 pandemic causes deteriorating psychological health in pregnant women. Worse psychological status can arise because lack of social support causes increased symptoms of anxiety and depression.Purpose : This study aims to identify the psychological impact that occurs on pregnant women during the COVID-19 pandemic.Methods: This type of research uses the literature review method from 8 journals in the PubMed, ScienceDirect, Tandfonline databases in the 2020 - 2021 period. Results: The results show that the COVID-19 pandemic can have a significant psychological impact on pregnant women, especially in the form of anxiety and symptoms of depression. The prevalence of depression in pregnant women has increased significantly to 35.3% in China and anxiety symptoms to 56.6% in Canada since the spread of the COVID-19 disease. Pregnant women during the COVID-19 pandemic reported more psychological symptoms than before the COVID-19 pandemic. The prevalence of depression and anxiety symptoms in pregnant women before the COVID-19 pandemic in Spain was 12.8% and 15.2%, respectively, increasing to 38% and 59% during the COVID-19 pandemic..Conclusion: Pregnant women are especially vulnerable to symptoms of anxiety and depression. The COVID-19 pandemic had negative psychological impacts on pregnant women. Family support and social support can overcome the causes of psychological problems in pregnant women, and early identification and intervention for mood symptoms in pregnant women during a pandemic is important to improve mental health care for pregnant women, especially considering the long-term adverse effects on the birth and development of the baby later.